PENGELOLAAN PASAR DESA TANJUNG SAWIT KECAMATAN TAPUNG KABUPATEN KAMPAR TAHUN 2017-2018 - Ahmad Syakirin; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Decree of the Kampar Regent No. 414-98 / I / 2018 regarding the surrender of the village market and the local government market in the village to the village government in Kampar District stated that Tapung District has 13 village markets whose management has been fully delegated to the local village government. One of them is the Tanjung Sawit village market. In 2017 the management of the village market in Kampar Regency is still under the authority of the local government of Kampar Regency. Entering 2018, the Kampar Regent's decision issued that village market management be left entirely to the village government. Tanjung Sawit village market has an area of 3 hectares (Ha) and is the oldest village market in Tapung District, Kampar Regency. Although the Tanjung Sawit village market is the oldest and widest market in Tapung Kanb Kecamatan Kampar District, its management is still not optimal in terms of planning, utilization, security and maintenance, as well as guidance and supervision.This study aims to determine the market management of Tanjung Sawit village in Tapung Subdistrict, Kampar Regency in 2017-2018 and find out and analyze the factors that are hampering the management of the Tanjung Sawit village market, namely: Vaccine management of Tanjung Sawit village market, the absence of village regulations regarding management village market, lack of budget for village market management, and lack of market management structureThe results of this study indicate that the management of the village market of Tanjung Sawit Tapung District, Kampar Regency is not optimal. Can be proven by the number of village market buildings that were badly damaged due to the absence of village market development planning, the lack of utilization of market infrastructure that caused the market retribution results in 2017 and 2018 to not reach the target, market security and maintenance that were not carried out optimally and the lack of guidance and supervision towards market management. Keywords : Management, Village Market